People Awakening: Collaborative Research to Develop Cultural Strategies for Prevention in Community Intervention. Issue 1 (6th June 2014) - Allen, James; Mohatt, Gerald V.; Beehler, Sarah; Rowe, Hillary L.
Abstract: The consequences of alcohol use disorder (AUD) and suicide create immense health disparities among Alaska Native people. The People Awakening project is a long‐term collaboration between Alaska Native (AN) communities and university researchers seeking to foster health equity through development of positive solutions to these disparities. These efforts initiated a research relationship that identified individual, family, and community protective factors from AUD and suicide. AN co‐researchers next expressed interest in translating these findings into intervention. This led to development of a strengths‐based community intervention that is the focus of the special issue. The intervention builds these protective factors to prevent AUD and suicide risk within AN youth, and their families and communities. This review provides a critical examination of existing literature and a brief history of work leading to the intervention research. These work efforts portray a shared commitment of university researchers and community members to function as co‐researchers, and to conduct research in accord with local Yup'ik cultural values. This imperative allowed the team to navigate several tensions we locate in a convergence of historical and contemporary ecological contextual factors inherent in AN tribal communities with countervailing constraints imposed by Western science.